Ethnic enclaves and welfare cultures: Quasi-experimental evidence - Olof Åslund; Peter Fredriksson (Institute for Labour Market Policy Evaluation (IFAU), 2005)
We examine peer effects in welfare use among immigrants to Sweden by exploiting a governmental refugee placement policy. We distinguish between the quantity of contacts – the number of individuals of the same ethnicity – and the quality of contacts – welfare use among members of the ethnic group. OLS regressions suggest that both these factors are positively related to individual welfare use. Instrumental variables estimations yield the conclusion that only the quality of contacts matter. An increase of the fraction of the ethnic group on welfare by 10 percent raises the individual probability of welfare use by almost 7 percent.
Keywords: I38; J15; J18; 330; Ethnic enclaves; welfare use; immigrants; Ethnische Gruppe; Sozialhilfeempfänger; Sozialethik; Schätzung; Schweden; Migranten; Segregation